Techno-economic and hybrid energy system analyses of hazelnut shell gasification based on geographical information system - Kirim, Yavuz; Yildiz, Ertugrul; Sadikoglu, Hasan; Melikoglu, Mehmet (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
In this study, electricity generation from hazelnut shells via gasification is studied in detail using Aspen Plus and economic analysis of the hazelnut gasification is thoroughly investigated. Novel to this study, hybrid energy generation potential of hazelnut shell gasification with different alternatives including PV are explored and H2 production from hazelnut shell is simulated in Aspen Plus. Mass flow of main outlet products (CO and H2) is 1103.43 kg/hr and 81.62 kg/hr, respectively. GIS is used to define the optimum area for the proposed hazelnut shell gasification plant. The production of syngas obtained from Aspen Plus simulation is estimated as 21,286,234 Nm3/yr, NPC and IRR values of the proposed gasification plant using method of time value of money are calculated as $106,673 and 28 %, respectively. NPC and COE of hybrid renewable energy system including battery storage are calculated as $6.87 M and $0.715, respectively.
Keywords: GIS; Hazelnut gasification; H 2 production; HRES; NPC; Techno-economic analysis; Computer Science; Engineering